The Growth of Beauveria bassiana on Corn Waste Medium - Dyah Rini Indriyanti; Siti Harnina Bintari; Ning Setiati; Puput Roy Purnawati (Universitas Negeri Semarang, 2022)
The purpose of this study was to analyze the density and viability of Beauveria bassiana grown on corn waste medium with 1% NPK (Nitrogen Phosphate Potassium) supplementation. This experimental study used a completely randomized design with 3 treatments and 9 repetitions. Each growth medium consisted of 25 grams of corn waste supplemented with NPK 1% with a dose of 0 mL (P0), 2mL (P1), and 3 mL (P2). The results of this study showed that the highest fungal density (16.72x108 conidia/mL) and viability (44.66%) were obtained from P2 treatment. It can be concluded that 1% NPK on corn waste medium affect the density and viability of Beauveria bassiana.